On a journey to citywide inclusive sanitation (CWIS)? A political economy analysis of container-based sanitation (CBS) in the fragmented (in)formal city - Mdee, Anna L.; Ofori, Alesia D.; Barrington, Dani J.; Anciano, Fiona; Dube, Mmeli; Hutchings, Paul; Kramer, Sasha; López-Valladares, Hellen; Parker, Alison; Riungu, Joy N.; Ward, Christopher (Taylor & Francis, 2025)
Rapidly growing cities face the chronic challenge of access to safe, dignified and accessible sanitation, in contexts of inequality and informality. Technological and operational innovations, such as container-based sanitation (CBS), are promoted as relatively low-cost market-based circular economy off-grid solutions to deliver citywide inclusive sanitation (CWIS). However, in the absence of evidence that CBS is delivering on these promises, this paper asks: under what conditions can CBS services contribute to achieving CWIS goals? It applies a combined political economy and socio-technical regime analysis to examine multi-level governance in the sanitation sector and CBS service regimes in Cape Town, Lima, Nairobi and Cap-Haitien. Only Cape Town, a municipality-controlled system, demonstrates the necessary public authority that enables CBS to operate at scale. Yet, it is regarded by many residents in informal settlements as poor sanitation for poor people. This suggests that scaling CBS requires sustained public investment and strong coordinating authority.
Keywords: Political economy; container-based sanitation (CBS); informal settlements; Governance; urbanization; citywide inclusive sanitation (CWIS); 4404 Development Studies; 4406 Human Geography; 4407 Policy and Administration; 44 Human Society